Identifikasi Faktor Penyebab Rendahnya Pemahaman Konsep Perkalian Pada Siswa Kelas IV SD Inpres 4 Lolu - ammar abdullah joni guci; difa isma wardani; nurul istiqamah; rayhanun diva gayahtri; tiara taha (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2026)
This study aims to identify the factors that cause the low understanding of multiplication concepts among fourth-grade students at SD Inpres 4 Lolu. Understanding multiplication concepts is an important foundation in elementary school mathematics learning because it influences students’ ability to learn more advanced mathematical material. However, in reality, many students still experience difficulties in understanding the concept of multiplication properly. This study used a qualitative approach with a descriptive method. The research subjects were fourth-grade students of SD Inpres 4 Lolu. Data were collected through observation, interviews, and documentation in the field to determine the level of students' understanding of multiplication concepts. The collected data were then analyzed to identify the factors that influence students' low understanding. The results of the study show that the low understanding of multiplication concepts is influenced by several factors, including the lack of understanding of the basic concept of repeated addition, less varied teaching methods, low student interest and learning motivation, and the limited use of instructional media that support conceptual understanding. In addition, the learning environment and the lack of practice also affect students' ability to understand multiplication concepts. Based on these findings, it can be concluded that improving students' understanding of multiplication concepts requires the use of more varied teaching methods, the use of engaging learning media, and sufficient practice so that students can better understand multiplication concepts.